2017
DOI: 10.1038/s41598-017-00246-0
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of a High-Density Genetic Map and Quantitative Trait Locus Mapping in the Manila clam Ruditapes philippinarum

Abstract: Genetic linkage maps are indispensable tools in a wide range of genetic and genomic research. With the advancement of genotyping-by-sequencing (GBS) methods, the construction of a high-density linkage maps has become achievable in marine organisms lacking sufficient genomic resources, such as mollusks. In this study, high-density linkage map was constructed for an ecologically and commercially important clam species, Ruditapes philippinarum. For the consensus linkage map, a total of 9658 markers spanning 1926.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Reduced-representation sequencing techniques such as GBS or RAD-seq will likely be important for future genomics-based selection in molluscs, as such techniques allow for pedigree reconstruction, estimation of trait heritability, genetic map construction, identification of QTL, and estimation of genomic breeding values in the same experiment (Palaiokostas et al, 2016 ; Robledo et al, 2017 ). QTL mapping studies involving GBS or RAD-seq have been published for scallops (Jiao et al, 2014 ), oysters (Li and He, 2014 ; Shi et al, 2014 ; Wang et al, 2016 ), clams (Nie et al, 2017 ), and abalone (Ren et al, 2016 ). Recently, the feasibility of GS using 2b-RAD (Wang et al, 2012 ) was demonstrated in an experiment involving Yesso scallops ( Patinopectin yessoensis ; Dou et al, 2016 ).…”
Section: Opportunities For Genomics-based Selectionmentioning
confidence: 99%
“…Reduced-representation sequencing techniques such as GBS or RAD-seq will likely be important for future genomics-based selection in molluscs, as such techniques allow for pedigree reconstruction, estimation of trait heritability, genetic map construction, identification of QTL, and estimation of genomic breeding values in the same experiment (Palaiokostas et al, 2016 ; Robledo et al, 2017 ). QTL mapping studies involving GBS or RAD-seq have been published for scallops (Jiao et al, 2014 ), oysters (Li and He, 2014 ; Shi et al, 2014 ; Wang et al, 2016 ), clams (Nie et al, 2017 ), and abalone (Ren et al, 2016 ). Recently, the feasibility of GS using 2b-RAD (Wang et al, 2012 ) was demonstrated in an experiment involving Yesso scallops ( Patinopectin yessoensis ; Dou et al, 2016 ).…”
Section: Opportunities For Genomics-based Selectionmentioning
confidence: 99%
“…High-density (HD) genetic maps provide information on genome organisation by establishing the cartography of thousands of markers, which can aid to disentangle the genetic architecture of productive or evolutionary traits. Moreover, these maps represent an essential tool for comparative genomics and can facilitate whole genome assembly 2 , 3 . The advent of next generation sequencing (NGS) has dramatically reduced the cost and time required for genomic analysis, 4 , 5 thus contributing to a fast increase of genomic resources.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in GBS technology have allowed the identification of numerous genetic molecular markers at a reasonable cost. This has promoted the development of several high-throughput single-nucleotide polymorphism (SNP) genotyping methods [ 23 ].…”
Section: Introductionmentioning
confidence: 99%